Mary Magdalene : Iconographic studies from the Middle ages to the Baroque - Erhardt, Michelle A.; Morris, Amy M. (Studies in Religion and the Arts, 2012)
Mary Magdalene, Iconographic Studies from the Middle Ages to the Baroque examines the iconographic inventions in Magdalene imagery and the contextual factors that shaped her representation in visual art from the fourteenth to the seventeenth centuries. Unique to other saints in the medieval lexicon, images of Mary Magdalene were altered over time to satisfy the changing needs of her patrons as well as her audience. By shedding light on the relationship between the Magdalene and her patrons, both corporate and private, as well as the religious institutions and regions where her imagery is found, this anthology reveals the flexibility of the Magdalene's character in art and, in essence, the reinvention of her iconography from one generation to the next.